Analisis Penerapan Hukum Ekonomi Syariah terhadap Skema Komisi dan Bonus pada Platform Evermos - Maharani, Dinda Fiachsania; Alifa, Rannan Salma; Andrian, Devi; J, Jaenudin; Herdiana, Dian (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the implementation of Islamic Economic Law principles on the commission and bonus schemes applied by Evermos, a sharia-based social commerce platform. Using a qualitative approach with descriptive-analytic methods, data were collected through documentation studies sourced from the Evermos official website, sustainability reports, DSN-MUI fatwas, and relevant muamalah literature. Data were examined using content analysis and normative comparison to assess sharia compliance. The results show that the commission system aligns with the akad wakālah bil ujrah, where resellers act as agents entitled to fair compensation based on their marketing performance. Meanwhile, the bonus scheme corresponds to the concept of ju‘ālah, permissible as long as it is transparent, free from gharar and maisir, and not structured as prohibited multi-level schemes. Overall, Evermos’ commission and bonus mechanisms meet the principles of justice, transparency, and maslahah required in Islamic Economic Law. The study contributes to the theoretical development of sharia business governance and offers practical recommendations for strengthening sharia compliance in digital commerce.